THE HISTORY OF THE MOSQUE OF ODINA (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The content of the article is that the history of the jome mosque in Odina and its transformation into a museum are given. Including mention of its architecture and exhibits.